Perlindungan Hukum Terhadap Jurnalis Korban Tindak Pidana Kekerasan Dalam Menjalankan Tugas Jurnalistik Di Kota Kupang - Tulle, Kevin Christian; Manuain, Orpa G; Dede, Ngongo (Law Faculty, Nusa Cendana University, 2025)
The persecution experienced by journalists is one of the crimes, the persecution of journalists is intended for legal protection of journalists from acts in the form of attacks on body parts or other parts that cause injury, even death. In Kupang City, several cases of persecution of the Press also occurred so widespread, one of the cases was